2021
DOI: 10.1016/j.omtn.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-99a regulates CD4+ T cell differentiation and attenuates experimental autoimmune encephalomyelitis by mTOR-mediated glycolysis

Abstract: Multiple microRNAs exhibit diverse functions to regulate inflammatory and autoimmune diseases. MicroRNA-99a (miR-99a) has been shown to be involved in adipose tissue inflammation and to be downregulated in the inflammatory lesions of autoimmune diseases rheumatoid arthritis and systemic lupus erythematosus. In this study, we found that miR-99a was downregulated in CD4 + T cells from experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis. Overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Accumulating research studies have indicated that abnormal miRNA profile is a distinguishing feature of RA, and some miRNAs have been confirmed to involve the development of this disease [ 16 ]. In this study, decreased miR-129-5p was observed in RA-FLSs compared with normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research studies have indicated that abnormal miRNA profile is a distinguishing feature of RA, and some miRNAs have been confirmed to involve the development of this disease [ 16 ]. In this study, decreased miR-129-5p was observed in RA-FLSs compared with normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-99a, that is frequently down-regulated in RA and SLE, mitigated the development of experimental autoimmune encephalomyelitis (EAE) in mice through the inhibition of mammalian target of rapamycin (mTOR)-dependent glycolysis [231]. Targeting glutamine metabolism is a potential treatment approach in SLE to inhibit plasmablast differentiation [232] and in cancer to overcome tumor immune evasion as well [233].…”
Section: Metabolism and Nutritionmentioning
confidence: 99%
“…Overexpression of miR-99a, another anti-inflammatory miRNA, alleviated EAE development by promoting Tregs and inhibiting Th1 cell differentiation through suppression of mechanistic target of rapamycin (mTOR)-regulated glycolysis in CD4+ T cells [ 137 ].…”
Section: Self-extracellular Nucleic Acids In Neuroinflammatory Diseasesmentioning
confidence: 99%